Knowledge, Attitude and Practice of Contraception in the Women of Reproductive Age in Civil Hospital Karachi (Medical Forum Monthly, 2023)
Objective: To determine the knowledge, attitude and practice of contraception among married women of reproductive age group at a tertiary care centre.Study Design: Cross-Sectional Study.Place and Duration of Study: This study was conducted at the Department of Obstetric and Gynecology, The Civil Hospital Karachi from September 2021 to March 2022.Materials and Methods: All patients who fulfilled the inclusion criteria and visited to Department of Obstetrics and Gynecology, Dow University of Health Sciences/ civil hospital, Karachi were included in the study. Informed consent was taken after explaining the risks and benefits of the study. All married women of age 18-45 years attending outpatient department were recruited for study including pregnant women. The outcome variables included knowledge, attitude and practice of contraception at the time of presentation. All the collected data was entered into the proforma and used electronically for research purpose.Results: Mean age of patients in this study was 28.19±5.95 years. Majority of patient belonged to rural areas i.e 59.9%. However the adequate knowledge and appropriate practice of contraception was observed in 59.9% women. The positive attitude regarding contraception was 46.3%.Conclusion: Majority of women have adequate knowledge and appropriate practice of contraception. However the positive attitudes towards contraception was low in married women of reproductive age.